Analisis Manajemen Risiko Pada UMKM Pertanian Menggunakan Pendekatan ISO31000 dan Matriks Risiko: Studi Kasus “Berkah Tani” - Anisa Roshy Rosdian; Aghnia Yasyfa; Hesti Hisani Latifah Hamdah; Sarah Mutia Azahra; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The agricultural sector faces various risks that can threaten business continuity and sustainability. This study aims to analyze risk management in agricultural MSMEs "Berkah Tani". This analysis was carried out using ISO 31000 standards, SWOT analysis and risk matrix. The results of the research are then used to formulate mitigation strategies to increase the resilience and sustainability of "Berkah Tani" agricultural MSMEs. A qualitative approach is used in this study because this study aims to understand in depth how agricultural MSME actors identify, assess and manage the risks faced in their business activities. The results of the study show that there are 6 risk categories in the Berkah Tani business, namely production, financial, marketing, market, human resources and legal risks. With a total of 19 events that occurred, of which 3 risks were at an extreme level, 8 were risks with a high level, 5 were risks with a medium level and 3 risks were with a low level.  This study confirms that risks in agricultural business are indeed high and can be threatening, but through planned and standardized risk management, Berkah Tani can improve its adaptability and maintain the sustainability of its business in the long term. .